Simplifying the complex : a guide to transition and activation planning for healthcare construction projects - Agner, Jeff; Aguilera, Lynn; Stevenson, Kathy (Emerald Publishing Limited, 2020)
Are you planning the Transition and Activation of a new healthcare project? This easy-to-use guide provides readers with the fundamentals of the transition, activation, and operational planning process and is essential for anyone involved in activating a new healthcare space. Developed by a highly experienced healthcare consulting company, Yellow Brick Consulting Inc., this straightforward planning roadmap tackles the high-risk and problem-prone strategic initiative of activating healthcare construction projects. Utilizing project management experience from healthcare projects of varying sizes, scopes and complexities, this book shares best practices and provides insight as to how to avoid common pitfalls through strategic planning. Simplifying the Complex provides the framework to establish a consistent process throughout the Transition and Activation Planning process, including project kickoff, budget development, building readiness, and people readiness. Each chapter guides the reader through the stages of the planning process and provides the tools necessary for implementing a successful project.
Includes index.
Keywords: Health facilities -- Design and construction.; Architecture, Buildings, Public, Commercial & Industrial.; Public buildings: civic, commercial, industrial, etc.; elektronické knihy; electronic books